Birth Certificate as Evidence Against A Child of Unknown Origin - Muhammad Akhyar (International Asia Of Law and Money Laundering (IAML), 2022)
The origin of a person is something that must be clear and true, since it is a clue to the identity of a person that must be fulfilled according to the legislation. One of the proofs of guaranteeing nasab that is accommodated by the national legal system is a birth certificate. A birth certificate can serve as a means of recognition submitted by parents. . This study discusses the proof of birth certificates of children whose origin is unknown through birth certificates.